Music Jaranan Turangga Yaksa in Dongko Village Trenggalek Regency (Study Ethnomusicology) - Varisandi, Syafiq Agil; Yuwana, Setya; Mariasa, I Nengah (Jurnal Seni Musik, 2023)
Jaranan Turangga Yaksa is an original art from Dhongko Village, Trenggalek Regency. Turangga Yaksa is a horse with a giant head and ridden by a knight who can control amarah, syaitonah, lauamah, dan serakah. This art is the result of creations from the Baritan ceremony (bar ngarit tanduran), local people usually hold tayub parties which aim to express gratitude for the harvest they have received. In this research, Jaranan Turangga Yaksa was studied ethnomusicologically by taking several approaches, namely describing the notation, musical aspects and organology found in the musical instrument Jaranan Turangga Yaksa. The research was conducted in Dhongko Village, Trenggalek Regency. The data collection method was carried out by interviewing several sources such as Mbah Mu'an (Creator of the Jaranan Turangga Yaksa music), chairman of the Sanggar Purwo Budaya, singer, dancer, and also pengrawit. Observe the development of musical accompaniment, and also perform FGD (Forum Group Duscussion) to deepen information and data to make it more valid. The description of the musical notation used by the author includes using number notation on balungan instruments and also vocals. The use of the terms plak, dlang, dhe as notation for percussion instruments such as kendang. Writing drum notation using notasi balok, and also using symbols as another term in writing gamelan notation. From the musical aspect, Jaranan Turangga Yaksa music has its own drum beats that differentiate it from other jaranan music such as Jaranan Buto, Jaranan Senterewe, Jaranan Pegon, and Jaranan Dor.